2019
DOI: 10.1039/c9cp04320a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic engineering of a tetrathiafulvalene charge-transfer salt via reduced symmetry induced by combined substituents

Abstract: A 1 : 1 metallic charge-transfer salt is obtained by cosublimation of (Z,E)-(SMe)2Me2TTF and TCNQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…All calculations included a Hubbard correction term Ueff = U − J = 6.0 eV for the sulfur 3p states. 65 In previous work 66 we have found that this U term on sulfur atoms is needed for appropriately describing the electronic structure of TTF-TCNQ and related molecular solids where accurate experimental information on the bandwidth and charge transfer is available. Only the valence electrons are considered in the calculation, with the core being replaced by norm-conserving scalar relativistic pseudopotentials 67 factorized in the Kleinman-Bylander form.…”
Section: Band Structure Calculationsmentioning
confidence: 99%
“…All calculations included a Hubbard correction term Ueff = U − J = 6.0 eV for the sulfur 3p states. 65 In previous work 66 we have found that this U term on sulfur atoms is needed for appropriately describing the electronic structure of TTF-TCNQ and related molecular solids where accurate experimental information on the bandwidth and charge transfer is available. Only the valence electrons are considered in the calculation, with the core being replaced by norm-conserving scalar relativistic pseudopotentials 67 factorized in the Kleinman-Bylander form.…”
Section: Band Structure Calculationsmentioning
confidence: 99%
“…All calculations included a Hubbard correction term Ueff = U − J = 6.0 eV for the S 3p and Se 4p states. 54 In previous work 55 we have found that this U term on the chalcogen atoms is needed for appropriately describing the electronic structure of molecular conductors were accurate experimental information on the bandwidth and charge transfer is available. Only the valence electrons are considered in the calculation, with the core being replaced by norm-conserving scalar relativistic pseudopotentials 56 factorized in the Kleinman-Bylander form.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…All calculations included a Hubbard correction term U e ff = 6.0 eV for the S 3p and Se 4p states . In a previous work, we have found that this U term on the chalcogen atoms is needed for appropriately describing the electronic structure of molecular conductors where accurate experimental information on the bandwidth and charge transfer is available. Only the valence electrons are considered in the calculation, with the core being replaced by norm-conserving scalar relativistic pseudopotentials factorized in the Kleinman–Bylander form .…”
Section: Methodsmentioning
confidence: 99%